(untitled) (ASEAN Engineering Journal, 2021)
Ureolytic bacteria strains of Bacillus show its ability of calcium carbonate precipitation through metabolic activity. Different studies related to self-healing concrete material were reported associated with the generated calcium carbonate of Bacillus subtilis HU58 metabolism in recent communications. In this paper, recent findings of soil cementing with a combination of such precipitated products were presented. The experiments relied on the lab-scale studies with the use of sand-clay mixture as the controlled soil specimens. Bacillus bacteria and nutrients were mixed to introduce in the sand matrix and then curing in high moisture condition. The composition and morphology of soil specimens were characterized after solidifying by FTIR, XRD, and SEM. Water percolation and mechanical stability for the physicomechanical properties were also tested with the unconventional method. Discussing the relevant results can help to figure out the next experiments in the field of geotechnical engineering. From the perspective of this study, the sustainability factor should be considered to apply this promising technique for soil stabilization and improvement and/or for the formulation of bio-brick as an alternative to sintered clay-based brick. From the perspective of this study, this technique for soil stabilization and improvement and/or for the formulation of bio-brick can be considered a promising sustainable alternative to sintered clay-based brick.